Correlation of Cultural Intelligence and Communication Skills of Pre and Post Covid Cohort Dental House Officers at Tertiary Care Hospital in Pakistan - Salima Naveed Manji, Muhammad Imtiaz, Malik Adeel Anwar, Khizer Mehmood, Maria Noor, Shahzad Ahmad, Romaysha Muzaffar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The present study aims to determine the correlation between cultural intelligence & communication skills of Pre and Post Covid Cohort of Dental House officers (DHOs) at Tertiary Care Hospital, Lahore Pakistan. Materials and Methods: The two-phase self–completion validated questionnaire-based correlational study was conducted on 120 dental house officers in two phases which includes Cultural Intelligence Scale (CQS) and Galasko Communication Skills Scale (GCSS) followed by dental house officer CQ & CS assessment via dentist-patient interaction done on ACIR communication skills scale. 60 DHOs were those who were given face-to-face patient interaction there was no COVID lockdown restriction are considered as Pre Covid Cohort. However, 60 DHOs were those who didn’t get the opportunity of face-to-face interaction with the patients due to COVID lockdown thus considered as Post Covid Cohort. Data were collected and entered in the excel sheet and transferred to SPSS for statistical analysis. SPSS 26.0 version was used. Results: Statistically significant differences between pre and post covid HOs responses and later their interaction with patients was found. The Pearson collection of CQ & CS in pre covid was 0.687 whereas the Pearson collection of CQ & CS in post covid was 0.549. Conclusion: Overall results indicate that face-to-face patient interactions, professional education on these competencies, reflective practice, and role modeling, with clearly associated learning objectives and assessments, will improve future cultural intelligence and communication skills curricula in oral and dental health programs thus emphasizing the need to include CQ & CS contents in formal dental curricula. Keywords: Cultural intelligence, Communication skills, dental house officers, virtual learning